2015
DOI: 10.1103/physreve.92.043020
|View full text |Cite
|
Sign up to set email alerts
|

Quasiperiodic routes to chaos in confined two-dimensional differential convection

Abstract: The complete cascade of bifurcations from steady to chaotic convection, as the Rayleigh number is varied, is considered numerically inside an air-filled differentially heated cavity. The system is assumed to be two-dimensional and is invariant under a generalized reflection about the center of the cavity. In the neighborhood of several codimension-two points, two main routes emerge, characterized by different symmetries of the first oscillatory eigenstate. Along these two competing routes, different sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Then a quasiperiodic regime with three incommensurable frequencies is identified at a Reynolds value of Re = 205. Sensitivity to the initial condition suggests that the present attractor is a stable torus T 3 , similar to that in [46]. The interpretation of this regime as a stable torus T 3 is not in contradiction with the Ruelle-Takens-Newhouse route to chaos since the latter does not exclude such nonchaotic states [47].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Then a quasiperiodic regime with three incommensurable frequencies is identified at a Reynolds value of Re = 205. Sensitivity to the initial condition suggests that the present attractor is a stable torus T 3 , similar to that in [46]. The interpretation of this regime as a stable torus T 3 is not in contradiction with the Ruelle-Takens-Newhouse route to chaos since the latter does not exclude such nonchaotic states [47].…”
Section: Discussionmentioning
confidence: 58%
“…This scenario is a typical Ruelle-Takens-Newhouse route to chaos, which has already appeared in several 064701-13 hydrodynamic examples (see, e.g., [18,20,25,44,45]). In particular, Oteski et al [46] reported this route to chaos including a stable three-frequency torus T 3 in a confined two-dimensional differential convection case. In the Ruelle-Takens-Newhouse scenario, the onset of the transition from a torus T 3 to a strange attractor is not predictable [47].…”
Section: Amplitude Fourier Spectrummentioning
confidence: 95%
“…A complete description of the transition to turbulence is given in Ref. [10] for air-filled 2D containers of Γ = 2, under a dynamical systems point of view. Two main routes that gradually break the symmetries of the solutions as sets were found.…”
Section: Introductionmentioning
confidence: 99%
“…We focus in this article on a model convection flow inside a two-dimensional cavity filled with air, heated on one lateral wall and cooled on the opposite wall, while the top and bottom walls are considered adiabatic. The cavity has a geometrical as-pect ratio height/width of two, and the flow is known to become oscillatory beyond a given value of the Rayleigh number Ra = Ra c = 1.5865 × 10 8 , where Ra is proportional to the temperature difference between the two walls 8 . Chaotic advection of non-diffusive tracers in the oscillatory regime has been considered numerically by Oteski et al 5 .…”
Section: Mixing Via Natural Convectionmentioning
confidence: 99%